Strategi Public Relation Dalam Membentuk Brand Awareness: Studi Kasus Website PT. Pasopati Insurance Broker - Noviana, Fience; Kurniawan, Fajar; Fajar, Adityo (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to analyze the public relations strategy implemented by PT. Pasopati Insurance Broker through its website as a means of building brand awareness among the public. The research adopts a descriptive qualitative approach using observation and interview methods to examine the effectiveness of the PR strategy in delivering information, managing the company’s image, and building relationships with the public. The results indicate that the PT. Pasopati website has been utilized as a corporate communication medium by presenting informative, educational, and promotional content related to insurance services. However, optimizing interaction and content actualization remain key challenges in achieving strong brand awareness.